Challenges of change facing entrepreneurs and Kuwaiti SMEs - Nouf Al Bazie (Taylor & Francis Group, 2020)
This research paper addresses a clear question: what are the critical factors that policy makers and entrepreneurs need to be aware of when operating in transitional economies in order to sustain SMEs? The SME sector is critically important to Kuwait’s transformation to a broad-based economy: one that is not reliant on oil alone. We studied Kuwaiti SMEs to identify criteria for change to survive in the nascent market. Our aim is to discuss these criteria in order to focus the attention of entrepreneurs and policy leaders. Policy makers should facilitate effective responses to change by SMEs; however, SMEs must address the challenges via effective change management. This process can be enhanced by policy makers promoting awareness of the factors discussed in this paper. Data was collected via interviews and a focus group with Kuwaiti entrepreneurs and policy makers. The data was analysed using qualitative methods to provide a rich picture of the criteria. We found seven factors that need to change in the Kuwaiti SME context. Our analysis yielded surprising results, such as SME CEOs’ lack commitment to their own business, and a lack of trust between entrepreneurs and their staff. Data collection was limited to the Kuwaiti SME sector.